2013
DOI: 10.4187/respcare.02201
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Physiological Response to Exercise in Patients With Different COPD Severity

Abstract: BACKGROUND: Patients with COPD have reduced exercise tolerance associated with dyspnea. This exercise intolerance is primarily due to impaired ventilatory mechanics, but it is also associated with a combination of factors, including inefficient gas exchange, lactic acidosis at a low work rate, and exercise-induced hypoxemia. The survival prognosis of COPD patients with severely reduced exercise capacity is extremely poor, but the pathophysiology of these patients during exercise remains to be accurately establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 36 publications
1
22
0
1
Order By: Relevance
“…Therefore, we cannot rule out the effect of skeletal muscle afferent activity on cortical activation. MAEKURA et al [34] found that the arterial pH decreased rapidly in COPD patients with severely reduced exercise capacity, and that their acidaemia was a result of both lactic acidosis and respiratory acidosis. We did not measure arterial lactic acid in this study, but increases in arterial lactic acid levels might have been different in the different groups of patients and might have resulted in different effects on cerebral metabolism or oxygen uptake [14].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we cannot rule out the effect of skeletal muscle afferent activity on cortical activation. MAEKURA et al [34] found that the arterial pH decreased rapidly in COPD patients with severely reduced exercise capacity, and that their acidaemia was a result of both lactic acidosis and respiratory acidosis. We did not measure arterial lactic acid in this study, but increases in arterial lactic acid levels might have been different in the different groups of patients and might have resulted in different effects on cerebral metabolism or oxygen uptake [14].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the PPR-OT program is for patients with advanced COPD to be able to safely live at home for a longer time without feeling breathlessness with their remaining cardiopulmonary capacity, which has been improved to the greatest extent possible by medication and PPR, including exercise training. As pathophysiological responses to exercise vary widely among patients with COPD, 10 we determined the safe range of activity for each patient, based on their CPET parameters. The criteria for a safe range were 1) PaO 2 >60 mmHg and 2) Borg scale score of <2 and/or lower than the norepinephrine (NE) threshold as there is a strong linear positive correlation between the NE threshold and the onset of dyspnea during incremental exercise.…”
Section: Methodsmentioning
confidence: 99%
“…The criteria for a safe range were 1) PaO 2 >60 mmHg and 2) Borg scale score of <2 and/or lower than the norepinephrine (NE) threshold as there is a strong linear positive correlation between the NE threshold and the onset of dyspnea during incremental exercise. 10 The safe range was identified by oxygen uptake (mL/min), which was determined according to each patient’s pulse oximeter O 2 saturation (SpO 2 ) (%) reading and pulse rate (beats/min) using a watch-type pulse oximeter, in addition to the Borg scale ( Figures 2 , S1 ). We designed this pulse oximeter in collaboration with Minolta Co Ltd (Hachioji City, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations